(untitled) (Economics and region, 2021)
The purpose of the article is to study the features of specialized tourism. The authors determined that the concept of "specialized tourism" in the scientific literature in Ukraine and around the world has been used for at least three decades. The article analyzes the essence of the concept of specialized tourism as a system of individual segments of tourism, based on the selection of which is the purpose of travel. It is established that specialized tourism offers a specific tourism product, which is focused on meeting the needs of specific market segments or niches and which is an alternative to mass tourism in the context of growing globalization. The main purpose of the trip is to satisfy certain special interests of tourists. It includes forms of tourism, focused and those activities that attract a small number of highly motivated tourists. As a result of the research it was determined that the development of specialized tourism is determined by the regional aspect and the available tourist resource potential. Specialized types of tourism are considered, which should be considered promising and priority for the Poltava region: health tourism (availability of a wide network of sanatoriums and balneological resources), cultural and cognitive (excursion) tourism, rural (green) tourism, religious (cultural) tourism, ethnic tourism, event (festival) tourism. The results of the research allowed us to conclude that the available tourist and recreational resources of Poltava region allow to focus on the joint development of health and rural (green) tourism, which will strengthen their competitive advantages. The article considers the concept of rural green tourism and its main varieties, in particular: green, rural, agritourism, eco-agritourism, agro-recreational tourism, etc. These types of tourism are considered as specialized and are promising types of tourist activities in Poltava region, the purpose of which is to implement specific requests of people during the trip, visiting destinations. Within these specialized types of tourism, special attention can be paid to a wide range of issues related to the study of culture, nature, as well as professional and various types of sports and leisure activities of tourists. Prospects for further research are to identify potential directions for the development of rural green tourism in the Poltava region.